Hãy nhập câu hỏi của bạn vào đây, nếu là tài khoản VIP, bạn sẽ được ưu tiên trả lời.
\(\left(x^2+4x-3\right)^2-5x.\left(x^2+4x-3\right)+6x^2\)
\(=\left[\left(x^2+4x-3\right)^2-2.\left(x^2+4x-3\right).2,5x+\left(2,5x\right)^2\right]-\left(0,5x\right)^2\)
\(=\left(x^2+4x-3-2,5x\right)^2-\left(0,5x\right)^2\)
\(=\left(x^2+4x-3-2,5x-0,5x\right).\left(x^2-4x-3-2,5x+0,5x\right)\)
\(=\left(x^2+x-3\right).\left(x^2+2x-3\right)\)
Tham khảo nhé~
\(x^8+3x^4+4\)
\(=\left(x^8-x^6+2x^4\right)+\left(x^6-x^4+2x^2\right)+\left(2x^4-2x^2+4\right)\)
\(=x^4\left(x^4-x^2+2\right)+x^2\left(x^4-x^2+2\right)+2\left(x^4-x^2+2\right)\)
\(=\left(x^4+x^2+2\right)\left(x^4-x^2+2\right)\)
\(4x^4+4x^3+5x^2+2x+1\)
\(=\left(4x^4+2x^3+2x^2\right)+\left(2x^3+x^2+x\right)+\left(2x^2+x+1\right)\)
\(=2x^2\left(2x^2+x+1\right)+x\left(2x^2+x+1\right)+\left(2x^2+x+1\right)\)
\(=\left(2x^2+x+1\right)^2\)
4x4 + 4x3 + 5x2 + 2x +1
= (4x4 + 4x3 + x2 ) + ( 2x2 + 1 ) + 1
= x2(2x + 1 )2 + 2x(2x + 1) +1
= (x(2x + 1 ) + 1)2
= (2x + x + 1)2
4x4+4x3+5x2+2x+1
=(4x4+4x3+x2) + (2x2+1) +1
= x2(2x+1)2 + 2x(2x+1) +1
= (x(2x+1)+1)2
=(2x2+x+1)2
\(x^5-5x^3+4x=x\left(x^4-5x^2+4\right)=x\left(x^4-x^2-4x^2+4\right)\)
\(=x\left[x^2\left(x^2-1\right)-4\left(x^2-1\right)\right]=x\left(x^2-1\right)\left(x^2-4\right)\)
\(=x\left(x-1\right)\left(x+1\right)\left(x-2\right)\left(x+2\right)\)
\(x^5-5x^3+4x=x^5-4x^3-x^3+\) \(4x\)
\(=\) \(x^3.\left(x^2-4\right)-x.\left(x^2-4\right)\)
\(=\left(x^3-x\right)\left(x^2-4\right)\)
\(=x\left(x^2-1\right)\left(x^2-4\right)\)
\(=x\left(x-1\right)\left(x+1\right)\left(x-2\right)\left(x+2\right)\)
\(x^3+y^3+z^3-3xyz\)
\(=\left(x+y\right)^3-3xy\left(x+y\right)+z^3-3xyz\)
\(=\left(x+y+z\right)\left[\left(x+y\right)^2-\left(x+y\right)z+z^2\right]-3xy\left(x+y+z\right)\)
\(=\left(x+y+z\right)\left(x^2+y^2+z^2-xy-yz-zx\right)\)
a)\(x^2-5x+4\)
\(=x^2-x-4x+4\)
\(=x\left(x-1\right)-4\left(x-1\right)\)
=\(\left(x-1\right)\left(x-4\right)\)
b)\(4x^2-4x-3\)
\(=4x^2+2x-6x-3\)
\(=2x\left(2x+1\right)-3\left(2x+1\right)\)
\(=\left(2x-3\right)\left(2x+1\right)\)
a) \(x^2-5x+4\)
\(=x^2-4x-x+4\)
\(=\left(x^2-4x+4\right)-x\)
\(=\left(x-2\right)^2-x\)
\(=\left(x-2\right)^2-\left(\sqrt{x}\right)^2\)
\(=\left(x-2-\sqrt{x}\right)\left(x-2+\sqrt{x}\right)\)
b) \(4x^2-4x-3\)
\(=4x^2-4x+1-4\)
\(=\left(2x+1\right)^2-2^2\)
\(=\left(2x+1-2\right)\left(2x+1+2\right)\)
\(=\left(2x-1\right)\left(2x+3\right)\)
Bài làm
\(x^3-5x^2-4x+20=x^2\left(x-5\right)-4\left(x-5\right)\)
\(=\left(x^2-4\right)\left(x-5\right)=\left(x-2\right)\left(x+2\right)\left(x-5\right)\)
\(x^3-5x^2-4x+20\)
\(=\left(x^3-5x^2\right)-\left(4x-20\right)\)
\(=x^2.\left(x-5\right)-4.\left(x-5\right)\)
\(=\left(x-5\right)\left(x^2-4\right)\)
\(=\left(x-5\right)\left(x-2\right)\left(x+2\right)\)